MiR-214-3p suppresses cervical cancer cell metastasis by downregulating THBS2: miR-214-3p inhibits cervical cancer metastasis - Wang, Xu; Xu, Jing; Hua, Fang; Wang, Yujing; Fang, Guiying; Zhang, Hongzhen; Wu, Xiaohua (Cellular and Molecular Biology, 2023)
Cervical cancer (CC) is the most common human gynecological malignancy worldwide. Recently, accumulating evidences revealed the critical functions of miRNAs in the occurrence and development of cervical cancer. In our study, we aimed to demonstrate the function of miR-214-3p in regulating cell metastasis in cervical cancer. We showed low expression of miR-214-3p in cervical cancer cells and demonstrated downregulation of miR-214-3p promoted cervical cancer metastasis. Furthermore, THBS2 was identified as a novel target of miR-214-3p in cervical cancer cells. miR-214-3p suppressed THBS2 expression by directly targeting 3’UTR of THBS2, resulting in the inhibition of cell viability, invasion and migration. Taken together, the results implied inhibited effects of miR-214-3p on cervical cancer and provided new insight into potential ways for cervical cancer diagnosis and treatment.